Facturación electrónica en Colombia: Una reflexión de sus efectos en el sector salud (2019)
The introduction of electronic invoicing is a fair and necessary measure imposed by governments in order to control tax evasion and improve tax management. In Latin American countries, especially Colombia, this phenomenon of evasion is more critical, so its implementation would lead to greater collection. This study was carried out with the objective of reflecting on the relevant aspects and how they would affect the electronic invoicing process to be implemented in 2020 for companies in the health sector in Colombia, in order to provide an overview of the situation that facilitates its analysis. Based on a bibliographic search on tax evasion in Latin America and the implementation of the model of electronic invoicing in health, a description of the relevant aspects for the implementation of the model of electronic invoicing in health was elaborated; which helped to conclude how the implementation of the model of electronic invoicing in Colombia is a fact, even though the regulations of the Ministry of Health and Social Pro-tection (Minsalud) and the irrectorate of National Ta-xes and Customs (DIAN) are not yet harmonized. This is why it is important to define together an electronic invoicing model that really allows them to achieve their objectives of controlling evasion, while at the same time being beneficial for all actors in the system.